Pengaruh Pengembangan Karir dan Kepuasan Kerja Terhadap Kinerja Pegawai pada Badan Pengelolaan Keuangan Pendapatan dan Aset Daerah Kota Sibolga - Ayu, Ayu; Hutagalung, Heriyawan; Sinaga, Nelly Azwarni (Yayasan Cita Cendekiawan Al Khwarizmi, 2024)
One resource that has a very important role in the progress of an organization is human resources. Therefore, every organization will always try to obtain quality human resources who are able to work effectively. HR's work commitment to the organization can grow if they have the opportunity to develop their careers. Apart from career development, organizations also need to pay attention to how the organization is able to provide job satisfaction for existing human resources. Like one government organization, namely the Sibolga City Regional Revenue and Asset Financial Management Agency, there are several problems that arise in employee career development and low levels of employee job satisfaction. The purpose of this research is to find out whether career development and job satisfaction influence employee performance at the Sibolga City Regional Revenue and Asset Financial Management Agency. The results of the research show that the results of the Validity test carried out show that the corrected item total correlation value is above the critical r value of 0.30, which means that all the question items for the two variables are declared valid. The results of the reliability test show that the Cronbach Alpha value obtained is above 0.6, so that all measuring instruments used are declared reliable and meet the requirements. The correlation coefficient shows a positive relationship between Career Development (X1) and Job Satisfaction (X2) with employee performance at the Sibolga City BPKPAD Office. The coefficient of determination obtained was 0.648, this means that career development and job satisfaction have an effect of 64.8%. From the results of testing the research hypothesis, it is stated that career development has an effect on employee performance at the Sibolga City Regional Revenue and Asset Financial Management Agency Office, which is proven and acceptable